Alteration of sensory-evoked metabolic and oscillatory activities in the olfactory bulb of GLAST-deficient mice - Martin, Claire; Houitte, Diane; Guillermier, Martine; Petit, Fanny; Bonvento, Gilles; Gurden, Hirac (Frontiers in Neural Circuits, 2012)
Astrocytes are key cellular elements in both the tripartite synapse and the neuro-vascular unit. To fulfill this dual role in synaptic activity and metabolism, they express a panel of receptors and transporters that sense glutamate. Among them, the GLT-1 and GLAST transporters are known to regulate extracellular glutamate concentrations at excitatory synapses and consequently modulate glutamate receptor signaling. These major uptake systems are also involved in energy supply to neurons. However, the functional role of GLAST in concurrent regulation of metabolic and neuronal activity is currently unknown. We took advantage of the attractive structural and functional features of the main olfactory bulb to explore the impact of GLAST on sensory information processing while probing both glutamate uptake and neuronal activity in glomeruli and deeper cellular layers respectively. Using odor-evoked 2-deoxyglucose imaging and local field potential recordings in GLAST knock-out mice, we show in vivo that deletion of GLAST alters both glucose uptake and neuronal oscillations in olfactory bulb networks.